Political Public Relations Campaign for Election of Mayor and Deputy Mayor of Solok Period 2016-2020 Division Community Relations and Event Coordinator - Elisabeth Putri Widasari; Agus Naryoso M.Si; Much Yulianto M.Si; Joyo M S Gono; Primada Qurrota Ayun (Interaksi Online, 2016)
The background of this field work is the winning pair Irzal Ilyas and Alfauzi Bote as Mayor and Deputy Mayor of Solok period 2016-2021 through the political campaigns of public relations. In the political campaigns of public relations, division of Community Relations and Event Coordinator tasked to establish relationships and conduct two-way communication with the religious leaders, community leaders, traditional leaders and communities through events, third party endorser, and community relations. Political public relations campaign lasted for two months and managed to make relations and support from religious leaders and traditional leaders in the 8 villages of 13 urban villages, 14 communities and 13 urban villages blusukan. In this field work also indicates that "Political Public Relations Campaign for Election of Mayor and Deputy Mayor of Solok Period 2016-2021" was successfully carried out.